Sistem Informasi E-Farming Berbasis Web Di Kabupaten Pinrang - Masnur, Masnur; Asra, Asra (Jurnal Sintaks Logika, 2021)
The purpose of writing this research is to design and build an E-Farming Information System and commodity crops. In conducting this research, researchers used an experimental method where the process begins with analyzing data requirements and developing existing systems. The initial data that you want to look for is by sharing information about this application in social media groups, both Facebook, WhatsApp and others who are domiciled in Pinrang. In addition, there is a system implementation and system maintenance, which in this case uses the PHP programming language as the backend language for this project. The results achieved from making the system with the data entered in the application using the Black Box method, it is found that the functional application runs well in accordance with the design made.